Silicone Materials for Electrical Insulation: A Dielectric Study of Oil Versus Gel - Haba, Yvonne; Gabriel, Jan P.; Thoms, Erik; Richert, Ranko (IEEE transactions on dielectrics and electrical insulation, 2022)
This work studies the dielectric characteristics of three insulators, two silicone oils, and a silicone-based gel, in order to assess their suitability as insulators under extreme environmental conditions. Permittivities are determined for frequencies between 0.1 Hz and 1 MHz and for temperatures ranging from −143 °C to +120 °C. The observed dielectric constants are practically frequency invariant and subject to only minor changes with temperature. These results are consistent with the dipole relaxation contributing only marginally to the dielectric properties of the oils and even less in the case of the gel. For one silicone oil, only very small changes in the dielectric constant are found for electric fields up to 165 kV/cm, consistent with the high dielectric strengths of these materials. The results will aid the design of high-voltage components that employ silicone-based insulators by providing the data necessary for finite-element simulations across a wide range of frequencies and temperatures.